Uji Aktivitas Ekstrak Perasan Daun Kedondong (Spondias dulcis) Sebagai Anti-Candida albicans pada Penderita Diabetes Melitus - Anita, Anita; Fatmawati, Andi; Widyanti, Tuty; Rahmawati, Rahmawati; Ahmad, Putri (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2023)
Diabetes is a disease characterized by high blood glucose levels which can stimulate the growth of the Candida albicans. Indonesia is the second highest country in the world with biodiversity which allows the creation of new compounds that can be used as medicine. One type of plant that has medicinal properties is kedondong leaves (Spondias dulcis) which can be used as herbal medicine, and can also act as an anti-fungal, because it has anti-fungal substances such as flavonoids, alkaloids, saponins and tannins. This compound can prevent fungal growth. The aim of this research was to determine the inhibitory ability of kedondong (Spondias dulcis) leaf extract in inhibiting the growth of Candida albicans using the Kirby Bauer method. The type of research used in this research is laboratory experiments. The results of the inhibition test in this study were the concentration inhibition zone results of 25%, 50%, 75%, 100%, the results were 0 mm, indicating that these 4 concentrations could not inhibit the growth of Candida albicans. Meanwhile, the positive control showed that there was a clear zone with an average of 28.8 mm, which indicated that antibiotics inhibited the growth of Candida albicans, while the negative control showed that no clear zone was formed. Therefore, the results of this study can be concluded that squeezed kedondong (Spondias dulcis) leaf extract cannot inhibit the growth of Candida albicans isolated from diabetes mellitus sufferers